Asian maths whizz and talkative females: how stereotypes can actually boost performance - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2009)
Nobody likes to be pigeonholed or reduced to a single stereotype. One reason could be because we believe ourselves to be products of multiple stereotypes: a combination of identities, such as "Asian", "female", "lawyer", "Gen X", "Christian", "Chinese", etc. While these labels connect us to like-individuals, they can also carry all sorts of connotations and expectations – positive, neutral and negative. For example, an Asian might be expected to outperform a non-Asian at mathematics because of stereotypes that Asians are mathematically inclined. Will such undue expectations affect the Asian's performance outcome? Research studies point to a 'Yes'.